Two-photon fluorescence imaging of mitochondrial superoxide anion transport mediating liver ischemia-reperfusion injury in mice. Issue 72 (21st August 2019) - Zhang, Wen; Su, Di; Li, Ping; Zhang, Jiao; Liu, Jihong; Wang, Hui; Zhang, Wei; Tang, Bo
Abstract : We constructed a new two-photon fluorescence ratio probe to reveal mitochondrial superoxide anion transport mediating liver ischemia-reperfusion injury in mice. Abstract : We constructed a two-photon fluorescence ratio probe (CST) for in situ quantitative real-time detection of mitochondrial O2 ˙ − . Fluorescence imaging showed that O2 ˙ − was over-generated from mitochondria and conveyed to the cytoplasm via voltage-dependent anion channels in hepatic ischemia-reperfusion mice, damaging the important functional protein aconitase in the cytoplasm.